Pemberdayaan Karyawan Sebagai Salah Satu Cara Meningkatkan Kinerja Perusahaan - Ria Satyarini (Center for Economic Studies Universitas Katolik Parahyangan, 1999)
Employees are internal customers for the company. By looking at the salary and fringe benefits accepted by the employees, there are only few companies that could satisfy these internal customers. Another way to increase employee's satisfaction is to implement an employee empowerment program, which means involvement of the employees in every step of the production process, including the delegation of decision making and responsibility. This paper will attempt to provide an adequate description of employee empowerment program and its benefits in increasing employees' motivation and working spirit. Furthermore, employee empowerment will also increase the effectivity of the company as well as improve the customer services. In implementing employee empowerment, the company has to create a conducive internal atmosphere, namely: trust and open management.